2007
DOI: 10.1111/j.1442-2042.2007.01844.x
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of darbepoetin alfa on experimental testicular torsion and detorsion injury

Abstract: Aim: Testicular torsion is a serious urological emergency, usually involving newborns, children, and adolescents which can lead to subfertility and infertility. Prevention of testicular damage caused by torsion is still a clinical and experimental problem. So far many chemicals and drugs have been investigated for decreasing ischemia/reperfusion (I/R) injury in experimental animals. The possible protective effect of darbepoetin alfa, a novel erythropoietic protein, on testicular tissue after I/R injury was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 49 publications
(92 reference statements)
0
22
0
Order By: Relevance
“…Although recently three publications have shown the possible beneficial effects of EPO in TT [15][16][17], the present study contains substantial new aspects in this field. Recently published studies have shown an anti-apoptotic and anti-inflammatory effect of EPO [15] and its free radical scavenger's activity, which decreases lipid peroxidation levels and the attenuation of apoptosis [16].…”
Section: Discussionmentioning
confidence: 86%
“…Although recently three publications have shown the possible beneficial effects of EPO in TT [15][16][17], the present study contains substantial new aspects in this field. Recently published studies have shown an anti-apoptotic and anti-inflammatory effect of EPO [15] and its free radical scavenger's activity, which decreases lipid peroxidation levels and the attenuation of apoptosis [16].…”
Section: Discussionmentioning
confidence: 86%
“…It has been known that the EPO-R, being widespread area of the body, has a regulative role for the survival and proliferation of testes cells [12,14] . The EPO is produced within the layer of germ cells in humans and involved in reproductive function of the testis [10] .…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to the findings of Çeribaşı et al [33] , indicating the occurrence of LPO in the cellular membranes within the testes [31,32] . Researchers reported that the DP administration reduces the high MDA levels of testes subjected to the IR in rats [14] . Both the DP and DP+RAM treatments prevented the increase in the MDA level caused by the DXR injection herein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPO-R have been detected in different types of tissue including brain, spinal cord, heart and testes, and exhibit neuroprotective, anti-apoptotic, antioxidant, anti-inflammatory and angiogenic activity (19). EPO and the long acting EPO analogue darbepoetin alfa may have a protective effect on testicular I/R injury (20,21).…”
Section: Agonists Of Erythropoietin Receptors (Epo-r)mentioning
confidence: 99%